PENGARUH BUDAYA ORGANISASI, KERJASAMA, LOYALITAS DAN KOMPETENSI TERHADAP KINERJA PEGAWAI KOORDINATOR LAYANAN ADMINISTRASI SATUAN PENDIDIKAN (KORMIN) KABUPATEN SUKOHARJO - Dyah Kusumo Sugih Hesti; Ida Aryati DPW; Sudarwati (ITB AAS Indonesia Surakarta, 2025)
The purpose of this study is to determine the partial and simultaneous influence of organizational culture, cooperation, loyalty, and competence on the performance of the coordinators of administrative services for educational units (Kormin) in Sukoharjo Regency. This study was conducted at the Department of Education and Culture of Sukoharjo Regency. It is a correlational study aimed at explaining the asymmetric relationships among the researched variables. The sample consisted of 55 employees working as coordinators of administrative services for educational units (Kormin) in Sukoharjo Regency. Data collection techniques included questionnaires, interviews, observations, and documentation. Data analysis techniques used were multiple regression tests, F-tests, t-tests, and the coefficient of determination (R²) test. The results of the study indicate that organizational culture, cooperation, loyalty, and competence have both partial and simultaneous effects on the performance of the coordinators of administrative services for educational units (Kormin) in Sukoharjo Regency. The Adjusted R Square (R²) value is 0.739 or 73.9%, which means that collectively, the independent variables—Organizational Culture (X1), Cooperation (X2), Loyalty (X3), and Competence (X4)—influence the performance (Y) of the coordinators by 73.9%, while the remaining 26.1% is influenced by other factors not examined in this study, such as work environment, organizational culture, rewards, and others. Keywords: Organizational Culture, Cooperation, Loyalty, Competence, Performance